1991
DOI: 10.1128/mcb.11.4.2189
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of Sp1 in the mouse.

Abstract: The expression of the trans-acting transcription factor Spl in mice was defined by a combination of RNA analysis and immunohistochemical localization of the Spl protein. Although ubiquitously expressed, there was an unexpected difference of at least 100-fold in the amount of Spl message in different cell types. Spl protein levels showed corresponding marked differences. Substantial variations in Spl expression were also found in some cell types at different stages of development. Spl levels appeared to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
314
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(330 citation statements)
references
References 25 publications
16
314
0
Order By: Relevance
“…Several transcription factors, such as GATA, Oct-1, or Sp1, can bind the CpG island. In particular, Sp1 is a ubiquitously expressed zinc-finger transcription factor that supports mRNA expression in a variety of eukaryotic genes that lack the functional TATA box (17,18). Among Sp family proteins, Sp1 and Sp3 were shown to be ubiquitously expressed in human tissues, and transcriptional activity enhanced by Sp1 was shown to be suppressed by Sp3 (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transcription factors, such as GATA, Oct-1, or Sp1, can bind the CpG island. In particular, Sp1 is a ubiquitously expressed zinc-finger transcription factor that supports mRNA expression in a variety of eukaryotic genes that lack the functional TATA box (17,18). Among Sp family proteins, Sp1 and Sp3 were shown to be ubiquitously expressed in human tissues, and transcriptional activity enhanced by Sp1 was shown to be suppressed by Sp3 (32).…”
Section: Discussionmentioning
confidence: 99%
“…DR-3 is a member of the apoptosis-inducing tumor necrosis factor (TNF) receptor superfamily that includes Fas (12)(13)(14)(15)(16), and its promoter region near the translation start site contains GATA, Oct-1, and two Sp1 binding sites, but without containing either the TATA or the CAAT box. Sp1 is a ubiquitously expressed zinc-finger transcription factor that supports messenger RNA (mRNA) expression in a variety of eukaryotic genes that lack a functional TATA box (17,18), and this may be important for synovial cell activation.…”
mentioning
confidence: 99%
“…However, the promoter activity of dynamin I, which seems to be strongly dependent on the ubiquitously expressed Sp1 and NEBP, might be regulated in a tissue-specific manner by these factors in several ways. The first possibility is the availability of these factors ; Saffer et al [41] showed that the levels of Sp1 protein vary between different tissues. They showed that Sp1 expression varies greatly in different cell types and that changes in Sp1 levels occur during development.…”
Section: Discussionmentioning
confidence: 99%
“…In the bovine SOD-2 gene the Spl sites have been shown to be necessary for basal promoter function, but not sufficient for conferring responsiveness to lipopotysaccharide. Furthermore, the Spl transcription factor has been shown to be regulated developmentally (264). It is, for example, known that Spl sites regulate the developmental expresssion of both the mouse secretory protease inhibitor p12 (265) and the murine deaminase gene (266).…”
Section: Su Peroxide Dism Utase and Oxidative Stress In Development Amentioning
confidence: 99%